Penerapan Metode LSM (Linier Scheduling Method) Pada Pembangunan Proyek Konstruksi (Studi Kasus: Perumahan Citra Agrindo III) - Vetry M. Gobel; Moh Yusuf Tuloli; Arfan Usman Sumaga (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Efficient scheduling methods are crucial in housing construction projects to minimize delays and optimize time management. This study investigates the impact of scheduling methods on project duration, highlighting the inefficiencies caused by mismatches between scheduling techniques and project characteristics. The research focuses on implementing the Linear Scheduling Method (LSM) for housing project scheduling and comparing it with conventional scheduling methods. LSM is particularly effective for repetitive construction projects, as it enables continuous work progression and minimizes task interference. By systematically organizing workgroups and sequencing activities, LSM ensures smoother workflow transitions and reduces idle time. A case study on the Citra Agrindo III Housing Project reveals that using LSM significantly improves time efficiency. The completion time is reduced from 384 days to 207 days, demonstrating a remarkable 177-day reduction compared to the existing scheduling approach. The findings highlight LSM's advantages in managing project timelines more effectively by streamlining workflow, preventing overlapping activities, and optimizing resource allocation. This research underscores the importance of selecting appropriate scheduling methods based on project characteristics to achieve better efficiency. The application of LSM in housing project scheduling proves to be a more effective approach, offering substantial time savings and improved project execution. Future research can further explore LSM’s adaptability across different construction project scales and complexities to enhance its implementation in the industry.